Investigating the Environmental Effects of Economic Growth in African Economies (International Journal of Sustainable Development & World Policy, 2020)
Sustainable green environment, green innovation, and low-carbon economy are the top priorities of governments and global climate institutions. Indeed, the link between economic growth and environmental sustainability has been commonly discussed in the literature, with different outcomes. This paper endeavors to partly fill the research gap by using recent panel estimators to explore the long-run cointegration nexus between economic growth, trade openness, energy consumption, urbanization, and CO2 emissions (pollution). In terms of decision making, we further grouped the specified 25 newly emerging African nations into oil-exporting and non-oil exporting economies. The data collected are annual and cover the period from 1990 to 2015. The panel cross-sectional dependency and homogeneity results indicated that our selected variables are heavily interdependent across the various cross-sections in the long-run. Similarly, the panel unit root test and bootstrap cointegration estimates showed evidence of stationarity and long-run equilibrium connection between the chosen variables for all panels. The long-run panel estimates using the common correlated effects mean group approach shows that economic growth, energy usage, trade openness, and urbanization depicted a positive and substantial impact on long-run carbon emissions for all panels. The Dumitrescu and Hurlin non-causality results indicated a bidirectional causal relationship between income and pollution, energy consumption and pollution, urbanization, and pollution for all three panels. Likewise, except for the 25-countries panel, there was evidence of a feedback causality between trade openness and pollution. Our outcome further verified the EKC framework but with distinct threshold points for all three panels. Various policy scenarios are discussed.